Implementation of Criminal Law in Indonesia - Reda Manthovani (Faculty of Law, Merdeka University Surabaya, Indonesia, 2021)
The criminal law system is a procedure used to uphold the rule of law and restore order as a result of crimes – acts against the law, committed by mistake, and deserving of punishment. The research method used in this paper is normative juridical law research, namely legal research conducted by examining library materials consisting of primary legal materials, secondary legal materials, and tertiary legal materials. The purpose of this paper is to examine the implementation of the criminal law system in Indonesia. As for the results of the study, it shows that in the criminal system, sanctions are imposed if a person fulfills the elements of a criminal act as evidenced by the presence of malicious intent (mens rea) from the perpetrator.